ANALYZE OF RESULTS OF THE KOSOVO SWIMMERS ALONG EIGHT YEAR PERIOD, BREASTSTROKE TECHNIQUE AT DISCIPLINES 50 AND 200 METERS - Ilir Gllareva; Besim Halilaj; Afrim Koca (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2014)
The study has had the aim to analyze swimming at several competitions of Kosovo swimmers through eight years period from 2002 to 2009 respectively 2003 to 2009, analyzing them in two different swimming disciplines - breaststroke at 50 and 200 meters swim distance by senior swimmers. There was increase in the value of the best annual results as a result of the distribution of outcomes within groups that have average scores represent values statistically insignificant, except from 2002 to 2008, in the 50m breaststroke. In the 200m breaststroke discipline noted that changes in the period 2003-2009 are too small as a whole. Through ANOVA method note that the average results in 50m breaststroke discipline is projected linear with only one statistically significant difference from 2002 to 2008 at level 0.05.